Analisa Implementasi Transformasi Digital Sistem Kerja Dalam Meningkatkan Kinerja Karyawan Pada Perusahaan Engineering, Procurement & Construction (EPC) - Ramdhan, Sahid Mohamad; Lahindah, Laura (Green Publisher Indonesia, 2025)
Digital transformation in the workplace has become a key factor in enhancing organizational effectiveness and operational efficiency, including in the Engineering, Procurement, and Construction (EPC) sector. PT XYZ, an EPC company established in 2019, has implemented digital transformation through the use of a project management application, Asana. This study aims to analyze the implementation of digital work system transformation at PT XYZ and its impact on employee performance. The research adopts a descriptive qualitative approach with data collection techniques including in-depth interviews, participatory observation, and document analysis. Informants consist of six categories: Shareholders, Board of Directors (BoD), General Manager, Manager, Supervisor, and Functional Staff. The results show that the implementation of a digital work system via Asana has had a positive impact on work transparency, communication efficiency, inter-unit collaboration, and task progress tracking. Employee performance indicators such as timeliness, productivity, and adaptability have also improved. However, the implementation is not yet optimal due to challenges such as unequal utilization of Asana across departments, lack of role-based digital training, and the absence of an integrated performance evaluation system linked to Asana. This research recommends enhancing role-based digital training, providing selective premium access for strategic-level roles, standardizing the use of Asana across units, and developing a digital performance evaluation system. Additionally, adaptive leadership and a strengthened digital work culture are essential to support the overall success of digital transformation.